The Making of English Subtitle for Profile Movie of Padang Pariaman Regency by Using The Aegisub Application - Yogi Rahmad; Desi Yulastri; Hendro Saptopramono (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2018)
This report discusses the process of making English subtitle by using the Aegisub application for profile movie of Padang Pariaman Regency produced by local government. The aims of making the English Subtitle for the profile movie is to influence the foreigners to visit Padang Pariaman as the tourism destination and to make this place well known worldwide. The profile movie tells the hidden potential sectors of Padang Pariaman, including tourism spots, farm, plantations, marine resources, hospitality, culture and customs. There are three stages conducted in the process of making the English subtitle. The stages are transcription, translation, and subtitling. The transcript of the profile movie consist of 1200 words with 14 minutes, 36 seconds in duration. The translation process, methods, and procedures are applied. There are several procedures used in the translation stage such as transference, descriptive equivalent, modulation, transposition, and recognized translation Then, the English subtitle is created by using Aegisub application. So the result of this project is a new profile of Padang Pariaman Regency with the English subtitle. Hopefully, this profile movie can be understood by foreigners who have great interest to become potential visitors in the future.